Study of early P91 dual corrosion in steam and simulated combustion gases from a gas-fired boile (2021)
P91 ferritic steel pipes face dual environments during boilers operation: steam-side and fire-side. This P91 steel assessment differs from the dual studies performed to simulate coal-fired boilers -oxyfuel/steam atmospheres- since the fuel source is replaced by natural gas. This research work includes designing a device to reproduce dual corrosion studies at 650 °C and testing times up to 200 h. One coupon face was exposed to combustion gases while the other to steam. As a main result, the duplex's inner layer allowed to state that combustion gases overcome the steam oxidation rate by a factor of 1.6. Besides, we supplied physical-chemistry information about the surface and bulk of oxide layers by atomic force microscopy, scanning electron microscopy, x-ray photoelectron spectroscopy, and x-ray diffraction analysis. Thus, our experiments aimed to obtain data about the P91 early degradation under the simultaneous 72.73N2/8.30CO2/3.37O2/15.60H2O %mol and steam influence. We last for a future work the isolated evaluation of both environments to determine their role on the corrosion rate obtained in the current study.